Biowaste for SOFCs. (November 2016) - Papurello, Davide; Silvestri, Silvia; Tomasi, Luca; Belcari, Ilaria; Biasioli, Franco; Santarelli, Massimo
Abstract: Organic Fraction of Municipal Solid Waste was adopted to produce biogas to feed a SOFC generator. Several experimental tests were accomplished on the trace compounds monitoring with PTR-ToF-MS instrument. The main organic compounds detected with the instrument were: sulfurs, terpenes, carboxyls, carbonyls and siloxanes. Coupled to these tests SOFC experiments were accomplished investigating the slipover influence from sorbent materials of sulfurs, chlorines and siloxanes. Limiting factors were evidenced from sulfur, chlorine and siloxane impact on SOFC using an electrochemical impedance spectroscopy (EIS). Tolerable concentration level of single organic compounds appears to be below 1 ppm(v) for H2S and no concentration is tolerated for siloxanes.